Precipitation during high temperature aging of Al−Cu alloys: A multiscale analysis based on first principles calculations. (1st April 2019) - Liu, H.; Papadimitriou, I.; Lin, F.X.; LLorca, J.
Abstract: Precipitation during high temperature aging of Al−Cu alloys is analysed by means of the integration of classical nucleation theory and phase-field simulations into a multiscale modelling approach based on well-established thermodynamics principles. In particular, thermal stability of θ'', θ′ and θ precipitates was assessed from first principles calculations of the Helmholtz free energy while homogeneous and heterogeneous nucleation of θ'' and θ′ was analysed using classical nucleation theory. Precipitate growth was finally computed by means of a mesoscopic phase-field model. The model parameters that determine quantitatively the driving forces for each transformation were obtained by means of first principles calculations and computational thermodynamics. The predictions of the models were in good agreement with experimental results and provided a comprehensive understanding of the precipitation pathway in Al−Cu alloys. It is envisaged that the strategy presented in this investigation can be used in the future to design optimum microstructures based on the information of the different energy contributions obtained from first principles calculations. Graphical abstract: Image 1